RESPONSE OF MATURE TEA (CAMELLIA SINENSIS L.) TO NITROGEN DURING DIFFERENT SEASONS - Hamid, F. S.; Khan, B. M.; Waheed, A.; Ahmad, N.; Ahmad, T. (The Nucleus, 2020)
Field experiments were conducted on mature tea bushes of Chinese Qi-Men variety at two different altitudes (1000 and 1500 m) from sea level during three consecutive years from 1998 to 2000. Different levels of nitrogen with the basal dose of phosphorus and potassium were applied to seven years old tea bushes. Mother leaf sampling was carried out during plucking season for the period of study. The mother leaves were analysed for nitrogen, phosphorus and potassium. The results revealed that the tea plucking in different months had a significant effect on the absorption of nitrogen from the soil. High uptake of nitrogen was observed during the main growing season than dormant months. It was observed that the dose of 420 kg N ha–1 gave the good results to overcome the critical level of NPK in the uppermost mature tea leaf in different plucking seasons.